Creative Environment in the Classroom and Students’ Satisfaction with School - Raquel Barroso; Diana Dias (Revista Colombiana de Educación, 2023)
Creativity is recognized as a cross-cultural requirement for the twenty-first century. This article aimed to characterize the students’ representations of creative environment and to explore the associations between students’ perceptions of the creative environment at school and the participants’ satisfaction with school. The study population consisted of 526 parents and 526 students from the third grade of primary school, 250 females (47.5 %) and 276 males (52.5%), aged between 8 and 11 years old (m = 8.27, sd = 0.50). The data was collected in school context through a questionnaire built within the scope of the current research and the Climate for Creativity in the Classroom Questionnaire. The analysis was performed using a quantitative methodology. The parents and students were satisfied with the children’s school and the students perceived the classroom environment as creative. The students’ perceptions of the creative environment in their classroom predicted their satisfaction with multiple aspects of the school analysed. Results were compared with findings from previous research.